A Highly Effective Biomass-Derived Solid Acid Catalyst for Biodiesel Synthesis Through Esterification - Zhang, Songdang; Pan, Hu; Huang, Jinshu; Li, Yuncong; Zhang, Heng (Frontiers in Chemistry, 2022)
Efficient valorization of renewable liquid biomass for biodiesel production using the desirable biomass-based catalysts is being deemed to be an environmentally friendly process. Herein, a highly active biomass-based solid acid catalyst (SiO2@Cs-SO3H) with renewable chitosan as raw material through sulfonation procedure under the relatively mild condition was successfully manufactured. The SiO2@Cs-SO3H catalyst was systematically characterized, especially with a large specific surface area (21.82 m2/g) and acidity (3.47 mmol/g). The catalytic activity of SiO2@Cs-SO3H was evaluated by esterification of oleic acid (OA) and methanol for biodiesel production. The best biodiesel yield was acquired by Response Surface Methodology (RSM). The optimized reaction conditions were temperature of 92°C, time of 4.1 h, catalyst dosage of 6.8 wt%, and methanol to OA molar ratio of 31.4, respectively. In this case, the optimal experimental biodiesel yield was found to be 98.2%, which was close to that of the predicted value of 98.4%, indicating the good reliability of RSM employed in this study. Furthermore, SiO2@Cs-SO3H also exhibited good reusability in terms of five consecutive recycles with 87.0% biodiesel yield. As such, SiO2@Cs-SO3H can be considered and used as a bio-based sustainable catalyst of high-efficiency for biodiesel production.